Fiscal Reaction to Interest Payments-the Case of Serbia - Andric, Vladimir; Arsic, Milojko; Nojkovic, Aleksandra (Industrija, 2016)
We focus on the response of primary fiscal balance to interest payments and borrowing costs on Serbian public debt before, during and in the aftermath of the global financial crisis. Our analysis reveals: i) policy makers financed up to 50% of each percentage point increase in interest payments to GDP ratio with new public debt issuance; ii) the government has responded to rising interest payments and borrowing costs by reducing primary fiscal balance from the onset of the global financial crisis; iii) the response of primary fiscal balance to interest payments mimics the response of primary fiscal balance to the costs of borrowing; iv) fiscal austerity measures adopted after the breach of fiscal rule for public debt have been insufficient to stabilize fiscal policy stance in Serbia.
Keywords: Global Financial Crisis; Augmented Fiscal Reaction Function; Fiscal Sustainability; Serbia; Payments; Debt; Costs